a college graduate expects to earn a salary of 50000 during the first year after graduation and recieive a 3% raise every year for 10 years

Answers

Answer 1
Answer: 50,000(1.03)^10=Y is the equation you would use to solve this, and this is how to solve it:

50,000(1.03)^10
50,000(1.34)
67,000

so his salary after 10 years will be $67,000.00

Related Questions

Only deposit 4000 between two savings accounts one account paying 4% simple interest in the other page 2% in the end of one year only hair $140 in interest for both accounts how much money did Ernie deposit in the account that paid 4% interest
A toddler crawled 3 yards, stopped, then continued to crawl 11 more feet. How many feet did he travel in total?
How old am I if 400 reduced by 2 times my age is 244? (answer with steps)
Standing in your tree house, 50 feet off the ground, you look down at a 60° angle and notice a Frisbee. Approximately how many feet from the base of the tree is the Frisbee?
The volume of a triangular prism with base dimensions of 4 cm height and 10 cm base and a prism height of 15 cm is??

Use the Distributive
Property to rewrite 8(16) + 8(6). Then evaluate the
expression.

Answers

Answer:

see explanation

Step-by-step explanation:

8(16) + 8(6) ← factor out 8 from each term

= 8(16 + 6)

= 8(22)

= 8 × 22

= 176

An experiment consists of tossing a coin and drawing a card, with the card-drawing stage dependent on the result of the coin toss. If heads occurs, then a card is selected at random from the clubs and spades suits. If tails occurs, then a card is selected at random from the hearts and diamonds suits. What is the size of the sample space of this two-stage experiment?

Answers

well .5 for coin toss and with 52 cards in deck and clubs and spades makes it 26 so its 1/26 then those are your probabilities.

Answer:th answer is 7

Step-by-step explanation:

the answer is 7

For brainiest:):):):):):)

Answers

Answer:

4=12%

5=7

6=12.25

7=82%

8=15.36

Step-by-step explanation:

youre welcome

Let f(x) = x + 8 and g(x) = x2 − 6x − 7. Find f(g(2)).

Answers

Mathematical Work:
f(x)=x+8
g(x)=x2-6x-7
f(g(2))=(2^2-6(2)-7)+8
f(g(2))=(4-12-7)+8
f(g(2))=-7
Explanation:
f(x)=x+8
g(x)=x2-6x-7
f(g(2))=?
2 was given as the x for function g and when you substitute 2 into function g's equation(g(2)=(2^2-6(2)-7)=-15, you would get -15. The answer to function g would be the x for function f. Which would be f(-15)=-15+8 and the answer for f(g(2)) is -7.
f(x) = x + 8
g(x) = x² - 6x - 7

f(g(2)) = ((2)² - 6(2) - 7) + 8
f(g(2)) = (4 - 12 - 7) + 8
f(g(2)) = (-8 - 7) + 8
f(g(2)) = -15 + 8
f(g(2)) = -7

3/10 off the normal price 400

Answers

Answer: 120

Step-by-step explanation: 3/10=0.3

0.3*400=120

9/11= ?/22 need help please

Answers

9/11 equals 18/22 because when u r doing this 11 times 2 equals twent two and nine times two equals eighteen therefore the answer is 18/22.
9/11=x/22
times 22 both sides
(9*2)/1=(22x)/22
18=x
x=18